2010
DOI: 10.1111/j.1741-4520.2009.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

No association between severe constipation with related drug treatment in pregnant women and congenital abnormalities in their offspring: A population‐based case‐control study

Abstract: Constipation is a common pathological condition in pregnant women; nevertheless, its possible association with structural birth defects (i.e. congenital abnormalities [CA]) in their offspring has not been studied in controlled epidemiological studies. We evaluated the possible association between severe constipation with laxative treatment in pregnant women and congenital abnormalities in their offspring. The dataset of the population-based Hungarian Case-Control Surveillance System of Congenital Abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although some researches of Senna have found that it is effective in a short-term usage of constipation treatment in pregnancy [258][259][260] and does not have the teratogenic potential [261], intake of Senna during the pregnancy is allowed only in some countries like the USA.…”
Section: Sennamentioning
confidence: 99%
“…Although some researches of Senna have found that it is effective in a short-term usage of constipation treatment in pregnancy [258][259][260] and does not have the teratogenic potential [261], intake of Senna during the pregnancy is allowed only in some countries like the USA.…”
Section: Sennamentioning
confidence: 99%
“…No study has specifically addressed the teratogenic effects of cathartics; however, no congenital anomalies were seen among 22843 pregnant women treated with laxatives[95]. The FDA reclassified cathartics and laxative agents from category B to category X. Cathartics are associated with a risk of dehydration and electrolyte imbalance.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…In Japan, magnesium oxide (MgO) is used as an osmotic laxative ( Morishita et al, 2021 ). The second-line therapy is based on stimulant laxatives, mainly senna ( Ford, 2008 ; Ács et al, 2010 ). Stimulant laxatives include sennosides and senna glycosides (SG).…”
Section: Introductionmentioning
confidence: 99%